2008
DOI: 10.1186/1754-9493-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Complications and safety aspects of kyphoplasty for osteoporotic vertebral fractures: a prospective follow-up study in 102 consecutive patients

Abstract: The data from the present study imply that percutaneous kyphoplasty can be associated with severe intra- and postoperative complications. This minimal-invasive surgical procedure should therefore be performed exclusively by spine surgeons who have the capability of managing perioperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 57 publications
(57 reference statements)
2
44
1
1
Order By: Relevance
“…[1][2][3][4]8,11,18,19 Studies showed that it provides nearly immediate pain relief in over 80% of cases, thus allowing patients to mobilize postoperatively. 2,3,20 From 2009 to 2010, 3 randomized controlled trials concluded that there was no superiority of vertebroplasty over nonsurgical management, or over a sham procedure. 9,18,21,22 This led to restrictions of its use in North America.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4]8,11,18,19 Studies showed that it provides nearly immediate pain relief in over 80% of cases, thus allowing patients to mobilize postoperatively. 2,3,20 From 2009 to 2010, 3 randomized controlled trials concluded that there was no superiority of vertebroplasty over nonsurgical management, or over a sham procedure. 9,18,21,22 This led to restrictions of its use in North America.…”
Section: Discussionmentioning
confidence: 98%
“…The most common complications associated with vertebroplasty and kyphoplasty are uncontrolled bone cement leakage over the venous plexus, which can even result in a pulmonary embolism. Leakage of the cement into the epidural space might cause neurological damage and even paraplegia [10] [13] [35]. Due to the elevated risk of cement leakage into the epidural space, in fractures that involve the posterior vertebral wall, these two procedures should only be used with great caution [22].…”
Section: Discussionmentioning
confidence: 99%
“…The use of fast-setting calcium phosphate appears to represent a safe and efficient technique for filling the metaphyseal void and providing adequate support for the articular surface to prevent secondary subsidence [14,16]. However, as with any appealing new surgical technique, the early enthusiasm regarding potential benefits must be critically weighed against potential complications and the risk of inducing patient harm on the surgical “learning curve” until a new technique is well established and validated [21]. To date, the available evidence supporting the concept of balloon-guided reduction of tibial plateau fracture is restricted to cadaveric studies, anecdotal case reports, and “expert opinion” technical notes [14-18].…”
Section: Introductionmentioning
confidence: 99%